Cefepime/tazobactam as a new treatment option for multidrug resistant gram negative bacilli - Agarwal, Roshni; Agarwal, Vaibhav; Tewari, Anjali; Upadhyay, Parwati (International Journal of Research in Medical Sciences, 2019)
Background: Every time an antibiotic is used, whether appropriately or not, the probability of the development and spread of antibiotic resistant bacteria is increased. Thus, multidrug resistant bacteria particularly ESBL (Extended spectrum βlactamase), Amp C and carbapenemases producing gram negative bacilli have emerged as a major health problem all over the world. Considering new treatment options as a carbapenems sparing and resistance prevention modality, this study was aimed to know the in vitro susceptibility pattern of Cefepime/Tazobactam (CPM/TZ) in comparison to other β-Lactam/ β-Lactamase inhibitors (BL/BLI) and carbapenems against GNB. Methods: A prospective study was conducted on all clinical samples received for a period of about 1 year. Identification and susceptibility of all isolates was done by Vitek 2 Compact system. Susceptibility of CPM/ TZ was done by disc diffusion method on the basis of CLSI guidelines. Both fermenters (E. coli and Klebsiella pneumoniae) and non-fermenters (Acintobacter baumanii and Pseudomonas aeruginosa) were included in the study. Results: Out of 550 GNB isolates the most common was E. coli (61.8%), Acintobacter baumanii (16%), Klebsiella pneumoniae (14.9%) and Pseudomonas aeruginosa (7.3%). Cefepime/tazobactam had a much higher susceptibility of 68% compared to cefepime (28%). Among the BL/BLI combinations tested cefepime/tazobactam (68%) showed the maximum percentage of susceptibility followed by cefoperazone/sulbactam (61.5%) and piperacillin/tazobactam (57.6%). Amongst all GNB isolates cefepime/tazobactam (68%) sensitivity was very much comparable to imipenem (71.8%) and meropenem (69.6%). Conclusions: CPM/TZ exhibited the best in vitro activity in comparison to the other BL/BLI. This new combination of cefepime/tazobactam appears to be a promising alternative therapeutic option to carbapenems. Clinical studies are needed to confirm this in vitro study result.